The Historical Development of Commercial Detonators and A Review of the Methods Used to Compare Their Ability to Initiate High Explosives - Robert B. Hopler (International Society of Explosives Engineers, 1990)
To understand any technology it is necessary that a thorough background of how we got to the present stage is necessary. To do that with the subject of initiation devices we need to begin many hundreds of years ago.